2004
DOI: 10.1002/ajim.20113
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of workers exposed to ionizing radiation at the French National Electricity Company

Abstract: The mortality of workers exposed to ionizing radiation at the French National Electricity company is very low compared to the French national mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 39 publications
4
19
0
3
Order By: Relevance
“…Compared to the other French nuclear worker cohorts, our cohort included a larger proportion of workers with a cumulative dose above 200 mSv (3.2%) than EDF (0.4%) or CEA (0.4%), confirming higher exposure of contract workers to ionizing radiation than that of workers in the other two cohorts [Telle-Lamberton et al, 2004;Rogel et al, 2005]. The mean cumulative dose observed in our cohort was much higher (33.5 mSv) than in most of the studies on nuclear workers [19.4 mSv for the 15-country collaborative cohort study, 10 mSv in the American cohort of the Idaho National Laboratory, and 8.3 mSv in the CEA cohort, Cardis et al, 2007;Telle-Lamberton et al, 2007] due to the higher proportion of workers exposed to cumulative doses above 200 mSv.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Compared to the other French nuclear worker cohorts, our cohort included a larger proportion of workers with a cumulative dose above 200 mSv (3.2%) than EDF (0.4%) or CEA (0.4%), confirming higher exposure of contract workers to ionizing radiation than that of workers in the other two cohorts [Telle-Lamberton et al, 2004;Rogel et al, 2005]. The mean cumulative dose observed in our cohort was much higher (33.5 mSv) than in most of the studies on nuclear workers [19.4 mSv for the 15-country collaborative cohort study, 10 mSv in the American cohort of the Idaho National Laboratory, and 8.3 mSv in the CEA cohort, Cardis et al, 2007;Telle-Lamberton et al, 2007] due to the higher proportion of workers exposed to cumulative doses above 200 mSv.…”
Section: Discussionmentioning
confidence: 98%
“…The 15-country collaborative cohort study conducted by the International Agency for Research on Cancer (IARC) included 407,391 nuclear industry workers monitored individually for external radiation and showed a significant association between radiation dose and all-cause mortality ThierryChef et al, 2007;Vrijheid et al, 2007]. This study is the largest epidemiological study on the effects of low-dose protracted exposure to ionizing radiation to date and included two French nuclear worker cohorts: 58,320 workers employed for more than 1 year at the French Atomic Energy Commission (Commissariat à l'Energie Atomique, CEA) between 1946 and 22,395 individuals monitored for radiation exposure over a period of at least 1 year between 1961 and 1994 at Electricité de France (EDF) [Rogel et al, 2005]. Both French studies showed a very strong healthy worker effect (HWE) with standardized mortality ratios (SMRs) for all-cause mortality, respectively, equal to 0.72 and 0.48.…”
Section: Introductionmentioning
confidence: 99%
“…The French nuclear worker cohort results from the combination of two nuclear worker cohorts implemented in the 1990s, namely the CEA-AREVA NC cohort (Telle-Lamberton et al, 2007;Metz-Flamant et al, 2011b) that included 36 769 workers and the EDF cohort (Rogel et al, 2005;Laurent et al, 2010) that included 22 392 workers. In 2011, these two cohorts were pooled after handling overlapping individuals (Metz-Flamant et al, 2013).…”
Section: Study Populationmentioning
confidence: 99%
“…Additionally, the study showed an ERR of 1.93 per Sv for leukemia, a disease that may be associated with radiation exposure (Cardis et al, 2005b). Nevertheless, these findings were not confirmed in a later study of workers from the French National Electricity Company (Rogel et al, 2005), and neither in the study of the United Kingdom Atomic Energy Authority (Atkinson et al, 2004). Conversely, both studies showed a strong healthy worker effect (HWE).…”
Section: Introductionmentioning
confidence: 47%